Abortion, Full Faith and Credit, and the "Judicial Power" Under Article III: Does Article IV of the U.S. Constitution Require Sister-State Enforcement of Anti-Abortion Damages Awards? - Brilmayer, Lea (Columbia Journal of Gender and Law, 2024)
Interstate judgments enforcement is governed by the Full Faith and Credit Clause of Article IV of the Constitution, together with its implementing statute, 28 U.S.C. 1738. Although a highly technical area of the law, interstate judgments enforcement has important social repercussions for some very modern problems of great cultural significance. One of the currently significant applications is the interstate enforcement of judgments rendered in civil suits based on state anti-abortion laws. For example, Texas statute S.B. 8 gives anyone who wishes to sue a civil cause of action against persons who facilitate abortions. Even complete strangers to the abortion can decide to become a plaintiff in such an action and can sue for money “damages” despite having suffered no injury. Non-experts seem to have the impression that the Full Faith and Credit Clause presents an ironclad requirement that judgments of sister states must always be enforced. If that were the case, states that recognize reproductive freedom would be obliged to enforce judgments entered into in states like Texas, despite their strong public policy against such actions. This Article shows why this impression is mistaken. First, the full faith and credit principle has for centuries been subject to exceptions, several of which are potentially relevant in the reproductive freedom context. These include lack of subject matter jurisdiction, the public policy exception, and the penal law exception. In addition, a uniform law adopted in forty-eight states (the Uniform Enforcement of Foreign Judgments Act) permits the state enforcing the judgment to apply its own judgments law to an interstate enforcement proceeding. The enforcing state will therefore apply to foreign state judgments any exceptions to judgments enforcement law that it has as a general matter for its own domestic judgments. Second, and more importantly, the Clause and statute both contain an important qualification: they apply only to “judicial” actions. This exception prevents a state from requiring sister-state enforcement of decisions that do not meet the usual tests for a judicial “case or controversy” (as defined in Article III of the Constitution). Article III and Article IV both use the word “judicial” to specify the standard necessary for the exercise of federal power. These two neighboring constitutional provisions are supported by a common historical origin (they were drafted at the same time and by some of the same people at the constitutional drafting convention) and fulfill comparable functions. If the two constitutional provisions are treated the same, judgments under statutes like Texas S.B. 8 would not be given mandatory force in other states because such cases would not meet the standing requirement imposed by Article III.